AKUNTABILITAS PERENCANAAN DAN PENGANGGARAN KEUANGAN DESA - ambarwati ambarwati; Dwi Puji Rahayu (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2020)
Abstrack Village finance is all village rights and obligations that can be valued with money and everything in the form of money and goods related to the implementation of village rights and obligations (Law Number 6 of 2014 Article 71 paragraph 1). Village development planning is a stage of activity organized by the village government by involving the Village Consultative Body and elements of the community in a participatory manner to utilize and allocate village resources in order to achieve village development goals. The Village Government prepares Village Development planning in accordance with its authority, referring to District / City development planning. The Village Revenue and Expenditure Budget (APBDesa) is an important instrument that greatly determines the realization of good governance at the village level. The objectives of this study are: 1) To prove the influence of Planning on Village Financial Accountability. 2) To prove the effect of Budgeting on Village Financial Accountability. 3) To prove the influence of Village Financial Planning and Budgeting on Village Financial Accountability. The subject of this research is the village government in Nganjuk Regency. In this study using a quantitative descriptive method with an associative approach that aims to determine the effect or relationship between two or more variables. In this study the population is all villages in Nganjuk Regency with 264 villages. Determine the number of sample samples from a population using the Slovin formula with Inaccuracy Tolerance of 5%. In this study there were 159 villages in the sample. The sampling technique in this study is done randomly by stratified random sampling. The data collection technique in this study was using a questionnaire or questionnaire. The research instrument used in this study using a Likert Scale, with a Likert rating scale from 1 to 5. This study uses testing Validity and Instrument Reliability. Data Analysis Techniques in this study used the Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test. Measurement of descriptive statistics in this study using Linear Regression Analysis. To test the regression model and hypothesis using statistical tests, namely the T test and F test. The output targeted in this research plan is submitted to national ISSN journals. The research plan is supported by the Regional Government of Nganjuk Regency through the Village Community Government Service which is expected to also be continued as a village assistance activity in the context of community service. Keywords: Planning, Budgeting, Village Finance, accountability, Village Government